DESAIN TAMAN DENGAN KONSEP HEALING GARDEN PADA AREA NAPZA DI RUMAH SAKIT JIWA (RSJ) Dr. RADJIMAN WEDIODININGRAT LAWANG - Setyabudi, Irawan; Hastutiningtyas, Wahidyanti Rahayu; Nailufar, Balqis; Nuraini, Nuraini (http://arl-faperta.ipb.ac.id/, 2016)
Pressure from modern environment that many can lead to mental disorder. The mental disorders exist because it exceeds the individual psychological endurance. One healing efforts undertaken by the Mental Hospital is making the garden is good to motivate patients. However, in general the design of the garden is still monotonous and can only be enjoyed visually. Should the patient require the involvement of the experience of space, so it is necessary to reorder function better room like gardening area or play area. The purpose of this research is to create a healing garden design that can treat patients with mental disorders in the area of drug. The case study is applied to the area of drugs at the Mental Hospital Dr. Radjiman Wediodiningrat Lawang. This is because garden have not potentially on healing in people with mental disorders by drugs. The research method is qualitative with a three-pronged approach, namely the science of architecture, agriculture, and health sciences. Architectural approaches that achieved with the design process begins with reviewing social issues, led to the idea-concept to realize the plans to get the site plan. Agricultural science approach to the choice of plants and processing, and health sciences approach to evaluate the existing design to patient involvement. Targets are resolved in this study is to examine the problems in the garden psychiatric hospital by producing a draft in the form of working drawings garden. The conclusion of this study is the concept of eco-friendly garden design according to user needs a mental hospital with the concept of healing gardens or garden or healing garden therapies that can improve the patient's recovery